Rodzaje uprzedzeń właścicieli gospodarstw ogrodniczych do zrzeszania się w grupy producentów – przykład gminy Błędów - Olewnicki, Dawid; Rybak, Justyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
Producer groups are a form of integration of horticultural producers. The main advantages resulting from the association include lowering production costs, increasing the impact on the market and gaining competitive advantage. Despite these benefits, many producers still do not want to associate. The aim of this study was to investigate the types of prejudices discouraging horticultural farm owners from organizing themselves in groups of producers in the community of Błędów. The study was conducted in 2012, among the owners of horticultural businesses, not belonging to the producer groups. The factors that may act as a barrier to joint action were examined. According to the survey, 38% of respondents do not want to belong to a group, more than half of respondents are undecided, while only 16% expressed a desire for membership in the group. The main barriers of association may include economic, administrative, and psychological factors.